Perceptions of malaysian undergraduates on Bantuan Rakyat 1 Malaysia (BR1M) - Chong, Yenwan (2019)
In 2012, the Malaysian government initiated a cash handout scheme named BR1M which stands for 'Bantuan Rakyat 1 Malaysia' aimed at helping low-income Malaysian households. In recent months, there has been a lot of debate on BR1M. This paper aims to examine the views of millennials on whether BR1M is a good policy for Malaysia. Seeking the views of Malaysian millennials on this topic is important because there is a lack of research on the perceptions of young Malaysians on this issue. It is also in line with recent calls by leaders in the government, society and academia on the need to encourage Malaysian youths particularly graduates and undergraduates to actively channel their ideas on important issues to help develop our country. This study found that slightly more than half, i.e 58.2% of Malaysian millennials agree that BR1M is a good policy for Malaysia. While most Malaysian millennials are supportive of BR1M, they have also highlighted a number of concerns with regard to BR1M. Among their major concerns are that BR1M may have long term negative effects on the country and that BR1M may also promote a dependency mentality and be a disincentive for the recipients to look for work. As pointed out by one respondent, “BR1M should be improved in the future to avoid abuse and incentivizing laziness or complacency. Government should also provide more career opportunities for the people rather than just giving cash hand-outs